Dynamic Behavior of a Beam Lying on a Generalized Elastic Foundation and Subject to a Moving Load - Erofeev, V. I.; Lisenkova, E. E.; Tsarev, I. S. (Mechanics of solids, 2021)
The analysis of the most famous elastic foundation models is presented. It is shown that, despite their different names, this is about the same generalized model characterized by two coefficients. Such a model allows not only preserving the simplicity of the mathematical apparatus inherent to the Winkler model, but also obtaining more reliable results. The consistent dynamic behavior of a beam lying on the generalized elastic foundation characterized by two foundation moduli (the compression coefficient and the shear coefficient) and subject to a moving load is considered. The features of the generation of bending waves by a moving load are studied and the critical speeds of its motion are determined. An expression for the pressure of waves (motion resistance force) is obtained. The dependence of the constant component of this force on the object speed is investigated. A comparison with the results obtained using the classical model of elastic foundation is presented.